2007
DOI: 10.1016/j.surfcoat.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the platinum effect on the oxidation behavior of nickel-aluminide coatings

Abstract: Oxidation resistant nickel-aluminide coatings are designed to develop a protective alumina scale during high temperature exposure. It is well established that platinum additions, typically about 6-8 at%, provide substantial improvements in oxidation resistance of such coatings, yet the nature of the platinum effect is still not fully understood. In this work, the oxidation behavior of two commercial NiAl and NiPtAl coatings deposited on the same Ni-base single crystal alloy CMSX-4 was analyzed.Cyclic and isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Experimental results on model alloys [18] and coatings [46] have indeed shown that Pt eliminates S segregation on bNiAl, and the current study shows that it reduces S segregation on c ? c 0 alloys, but there has not been any clear indications as to how such effects are achieved, and why the effects are alloy phase dependent.…”
Section: Segregation Behaviorsupporting
confidence: 74%
“…Experimental results on model alloys [18] and coatings [46] have indeed shown that Pt eliminates S segregation on bNiAl, and the current study shows that it reduces S segregation on c ? c 0 alloys, but there has not been any clear indications as to how such effects are achieved, and why the effects are alloy phase dependent.…”
Section: Segregation Behaviorsupporting
confidence: 74%
“…The effect of this enrichment might be to trap S in the metal, and as a consequence to limit the critical presence of S at the main metal/oxide interface. In this perspective, the results of this work are in agreement with the positive role of Pt for the TGO adherence as it is presented in the literature review [2,27,[35][36][37][38][39][40][41]. However, this work did not enabled an exact quantification of the amount of S at the metal/oxide interface.…”
Section: Study Of Sulfur Distribution In ''Commercial'' Tbc After Thesupporting
confidence: 84%
“…Compared to a non-modified coating, a gain in the adherence of the oxide scale is observed experimentally [2,26,[34][35][36][37]. The b-(Ni,Pt)Al coatings are currently used in the industry and their role in limiting the deleterious effect of S has been proven.…”
Section: Adopted Strategies To Counter the Sulfur Effectmentioning
confidence: 99%
“…1719) The mechanisms 20) that Pt promotes the formation of the Al 2 O 3 scale and the mechanism 18,21) that Pt improves the adhesion of the Al 2 O 3 scale have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Pt decreases the oxygen permeability into the alloy which decreases the critical Al concentration for Al 2 O 3 formation. Hou et al 18) claimed that the improvement in the adhesion of the Al 2 O 3 scale due to the Pt addition into Ni aluminide was attributed to the fact that S segregation at the scale/alloy interface was prevented by Pt. Cadoret et al 21) suggested that the improvement in the adhesion of the Al 2 O 3 scale due to Pt addition into Ni aluminide resulted from the fact that Pt slowed down the Al 2 O 3 -scale transformation from a metastable phase (ª phase) to a stable phase (¡ phase), and as a consequence, such a transformation lag decreases the stress evolved in the scale.…”
Section: Discussionmentioning
confidence: 99%